Hierarchy of Needs Analysis of The Main Character of A Novel American Royals by Katharine McGee - Silfanah, Riski; Luthfiyah Adiiibah, Salsabiila; Tri Santosa, Budi (Universitas Muhammadiyah Semarang, 2024)
Cheating in violation of norms is an act of betrayal of a partner that is caused by the fading of normative values within the perpetrator. Cheating can make the victim disappointed and traumatized because they feel their trust has been destroyed by their partner. To collect the data, researchers used the documentation method. The final results of this research will be described descriptively in the form of words, phrases, sentences and paragraphs. Theory of Hierarchy of Needs by Abraham Maslow can be seen in the novel American Royals by Katharine McGee, there are many needs experience by physiological needs, safety needs, love needs, self-esteem and self-actualization. The result of this research is the physiological need that Beatrice needs is the fulfillment of the love needs. When the emotional of physiological needs are not contented it will be trigger negative mental issues and cause the impact on the individual. Furthermore, it not only damaging the mental health, but it can also affect someone’s physical health.